PERUBAHAN SIFAT FISIK DAN CITA RASA KOPI ARABIKA ASAL BONDOWOSO PADA BERBAGAI TINGKAT PENYANGRAIAN - Hasbi Mubarak Suud; Dyah Ayu Savitri; Safa Rajni Ismaya (Jurnal Agrotek Ummat, 2021)
Arabica coffee from the plantation on the foothill of Ijen-Raung mountains in Bondowoso is well known for its Java Arabica Coffee specialty. The exploration to strengthen the specialty identity is keep going on. This study aims to determine the changes in physical properties and flavor of that arabica coffee during roasting at various times and temperatures of roasting. The aspects of physical properties that were studied include weight to volume ratio, coffee bean dimension, and a color index of RGB (red green blue). The weight-to-volume ratio and color index of RGB decreased as the time and temperature roasting increased. The change in dimension of the coffee bean was caused by roasting also detected, but not dominant signifies the roasting level. This is due to the dimension change of coffee bean in each roasting profile having tiny differences and the dimension of the green bean had high variation. Based on this study, it is known that the roasting with a maximum temperature of 165°C and total time process of 9.5 minutes gives the highest total score of aroma, flavor, acidity, and aftertaste of that arabica coffee.